Prevalence and characteristics of accidental perineal tears during childbirth in a communal medical center in Guinea-Conakry: a cross-sectional study - Bah, Oumou Hawa; Diallo, Boubacar Alpha; Soumah, Aboubacar Fode Momo; Diallo, Boubacar Siddi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Prevalence studies are still rare in sub-Saharan Africa on perineal tears. We conducted this cross-sectional study in a communal hospital in Guinea-Conakry, with the objective of this study was to determining the prevalence and characteristics of post-obstetric perineal lesions.Methods: All deliveries between March 1st and August 31st, 2014 were reviewed. We included in the analysis all the single deliveries with perineal tears. The Anglo-Saxon classification of perineal tears was used.Results: The prevalence of perineal tears was 5.7% with 5.4% benign lesions and 0.3% severe lesions. We did not register 4th degree lesions. The average age of parturient was 22 years. The majority (96.6%) of parturient had a history of genital mutilation and perineal scarring (60.3%).Conclusions: This prevalence appear low compared to those reported in other studies in Africa and point to the need for more sophisticated studies to have a better estimate of the prevalence of perineal tears in Guinea-Conakry.